Wood density and fiber dimensions of Gmelina arborea in fast growth trees in Costa Rica: relation to the growth rate - Moya Roque, R.; Tomazello Fo, M. (Forest Systems, 2007)
The objective of this research was to determine growth rate effects measured in tree diameter on wood density parameters (mean, minimum, maximum and intra-ring variation) and in fiber dimensions (wall thickness, fiber width, lumen diameter and fiber length) of trees from fast growth plantations. Thirty mature trees were sampled from thirty different fast-growth plantations with a wide growth rate in Costa Rica. A disc was cut from each tree at DBH. The wood density parameters and fiber dimensions were determined in each growth ring. Some wood density parameters and fiber dimensions were related with growth rate. The minimum and mean density, cell wall thickness, fiber width and lumen diameter decreased with increase in growth rate. Intra-ring wood density variation increased with growth rate but the weak correlation was established. Maximum wood density was not found correlation with growth rate. A pronounced decrease was presented in minimum and mean density from 0 to 20 mm/year and after to 45 mm/year. A pronounced decrease and increase with increase in growth rate were presented in the fiber length and intra-ring wood density, respectively. Lumen diameter and fiber width presented few variations, until 40 mm/year; however, they showed decrease after this growth rate value.